A video-based discussion of movement disorders in paediatric anti NMDAR encephalitis: A case series from Eastern India. (March 2022) - Datta, Amlan Kusum; Ghosh, Prakash Chandra; Bera, Mitali; Mukherjee, Adreesh; Chaudhuri, Jasodhara; Pandit, Alak
Abstract: Purpose: The spectrum of movement disorders associated with anti N-Methyl-d -Aspartate-Receptor (NMDAR) encephalitis is myriad, particularly in children, possibilities of which were investigated from two tertiary care centres. Methods: A retrospective study was conducted in two tertiary referral centres in Eastern India, analysing data of 8 paediatric patients diagnosed as anti NMDAR encephalitis, presenting with one or more movement disorders (MDs). Results: All the patients were of Bengali ethnicity with a median age of 9 years (3–16 years) and with female predilection (62.5%). CSF pleocytosis was a common feature in all. Seizures were described in 62.5%% of patients with a solitary patient exhibiting abnormalities on brain imaging. 3 out of 8 (37.5%) of patients presented with a single MD while the remaining had more than one type. Oro-linguo-facial dyskinesias and dystonia (37.5% each) were the most common movement type followed by chorea (12.5%). Complex stereotypies, myoclonus and facial tics were noted in one patient each. All patients received pulse methyl prednisolone. Escalation to second line therapy in form of rituximab was done for 5 patients (62.5%). Following immunotherapy, hyperkinetic movements resolved in 50% of patients, with persistence of movements in one (12.5%). A mortality of 37.5% was noted. Median duration of follow up was 26 months, during which none of the patients had evidence of systemic neoplasm. Conclusion: MDs are a core feature of anti NMDAR encephalitis, particularly in the paediatric age group, understanding and characterization of which, is the key to early diagnosis and effective therapy Highlights: Movement disorders are a distinct feature of anti NMDAR encephalitis, particularly in paediatric age group. There is a wide spectrum of movement disorders often in combination, as elaborated in the illustrative videos. Early and prompt recognition of movement semiology is essential to initiate therapy at earliest. Anti NMDAR antibody mediated movement disorders may respond favourably to immunomodulation. Recognizing the movement disorders is important in resource limited situations to curtail cost of unnecessary investigations.